Literature Review: The Role of Local Wisdom-Based Physics Learning with Patil Lele in Enhancing Students' Scientific Literacy - Agustinaningrum, Nur Afni; Deta, Utama Alan (International Journal of Research and Community Empowerment, 2025)
According to PISA 2022, the level of scientific literacy among students in Indonesia is considered low. One contributing factor is the lack of contextual learning in science education. In line with the Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education), it is essential to ensure the provision of relevant education that is connected to real-life experiences. One way to create contextual learning is by integrating local wisdom into the learning process. This study aims to explore the role of Patil Lele as a form of local wisdom in enhancing students' scientific literacy. The research method used is a literature review. Data were collected by reviewing five previous studies related to the application of local wisdom in physics education. The collected data were analyzed using the principles of organization, synthesis, and identification. The findings reveal that Patil Lele can serve as an interactive learning medium, support students in understanding the relationships between physical quantities in real contexts, and provide opportunities to practice decision-making and problem-solving based on physics concepts. Therefore, it can be concluded that the integration of patil lele as a local wisdom approach plays a significant and positive role in improving students' scientific literacy.